2007
DOI: 10.1016/j.mcn.2007.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression and function of synaptotagmin 1 isoforms in Caenorhabditis elegans

Abstract: Synaptotagmin 1, encoded by the snt-1 gene in C. elegans, is a major synaptic vesicle protein containing two Ca 2+ -binding (C2) domains. Alternative splicing gives rise to two synaptotagmin 1 isoforms, designated SNT-1A and SNT-1B, which differ in amino acid sequence in the third, fourth, and fifth β-strands of the second C2 domain (C2B). We report here that expression of either SNT-1 isoform under control of a strong pan-neural promoter fully rescues the snt-1 null phenotype. Furthermore, C-terminal fusions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…We therefore examined UNC-41 localization in snt-1(md290) mutants; md290 is a null allele of snt-1 [33]. We found that endogenous UNC-41, as assayed by immunostaining, was localized to synapses (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…We therefore examined UNC-41 localization in snt-1(md290) mutants; md290 is a null allele of snt-1 [33]. We found that endogenous UNC-41, as assayed by immunostaining, was localized to synapses (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…To test this hypothesis, we replaced the signal peptide and N-terminal domain of SUP-1 with the analogous region from SNT-1/synaptotagmin (Nonet et al 1993;Mathews et al 2007), an unrelated synaptic vesicle protein with the same (type I) membrane topology. We found that this chimeric protein suppressed the unc-17(e245) mutant phenotype and restored BiFC fluorescence (Figure 8).…”
Section: The Transmembrane Domain Of Sup-1 Mediates Interaction With mentioning
confidence: 99%
“…In contrast, deletion of the lumenal region between the signal sequence and the TMD eliminated suppression and most of the BiFC fluorescence. The little remaining fluorescence was restricted to the cell bodies, presumably due to improper trafficking of the SUP-1 protein.To test this hypothesis, we replaced the signal peptide and N-terminal domain of SUP-1 with the analogous region from SNT-1/synaptotagmin (Nonet et al 1993;Mathews et al 2007), an unrelated synaptic vesicle protein with the same (type I) membrane topology. We found that this chimeric protein suppressed the unc-17(e245) mutant phenotype and restored BiFC fluorescence (Figure 8).…”
mentioning
confidence: 99%
“…Interestingly, sytI is also a target of A-to-I RNA editing in some insects and squid ( Reenan 2005 ; Yang et al 2008 ). In addition, sytI also undergoes exon duplication and alternative splicing or other functional wobble splicing in C. elegans and A. californica ( Nakhost et al 2004 ; Mathews et al 2007 ). These events provide another means to create subtle changes at posttranscriptional stages.…”
Section: Discussionmentioning
confidence: 99%